Effectiveness of provider strategies for the early recognition of clinical deterioration due to sepsis in pediatric patients: a systematic review protocol. (January 2017) - Patton, Lindsey; Young, Virginia
Abstract : Review question: The objective of this review is to determine the effectiveness of provider strategies for the early recognition of clinical deterioration due to sepsis in pediatric patients. Specifically, the review question is: among pediatric, hospitalized patients, up to 18 years of age, what is the effectiveness of clinical assessment compared with use of early recognition screening tools for the recognition of clinical deterioration due to sepsis?